Doom Spending Behavior Among Gen Z: The Influences of Lifestyle, Conformity, and E-Payment Technology - Dhita Aulia Rahmayanti; Agung Haryono; Agus Sumanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of lifestyle, conformity, and the adoption of electronic payment technology on doom spending behavior among Generation Z. The research was conducted on active undergraduate students of the Faculty of Economics and Business, Universitas Negeri Malang, who belong to Generation Z, with a total of 134 respondents. A quantitative approach was employed using a survey method, and the data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results indicate that lifestyle, conformity, and the adoption of electronic payment technology each have a significant partial effect on doom spending behavior. These findings suggest that unplanned and excessive spending behavior (doom spending) among Generation Z is driven by a consumerist lifestyle, social pressure to conform, and the ease of transactions provided by electronic payment systems. This study highlights the importance of enhancing financial literacy and fostering critical awareness of social and technological influences in financial decision-making among the younger generation.